1985
DOI: 10.1152/ajpheart.1985.248.4.h438
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular function of the isolated, genetically obese rat's heart

Abstract: We sought to determine if left ventricular (LV) function of the heart from the adult, chronically obese animal is impaired. Hearts from 50 wk-old genetically obese female Zucker rats (624 +/- 13 g) and their lean littermate controls (275 +/- 5 g) were isolated during ether anesthesia, supported metabolically by retrograde aortic perfusion (6 ml/min, 35 degrees C) with physiological solution containing suspended canine erythrocytes (hematocrit, 20%), and the ventricles were paced at 180 beats/min. A distensible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
3

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 0 publications
0
15
0
3
Order By: Relevance
“…8,18 However, noninvasive methods such as echocardiography are limited in the extent to which mechanisms underlying these abnormalities can be identified. Animal models of obesity also have yielded little concrete information on the potential role of obesity in altering diastolic compliance, because of either contradictory results 19,20 or use of an animal model with many characteristics that are clearly different from human obesity. 19 -21 The rabbit model has been shown to be useful in the study of obesity-related hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…8,18 However, noninvasive methods such as echocardiography are limited in the extent to which mechanisms underlying these abnormalities can be identified. Animal models of obesity also have yielded little concrete information on the potential role of obesity in altering diastolic compliance, because of either contradictory results 19,20 or use of an animal model with many characteristics that are clearly different from human obesity. 19 -21 The rabbit model has been shown to be useful in the study of obesity-related hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Paradise et al, 7 studying the same model at 11 to 13 months, found diminished values of unnormalized wall stress, suggesting either reduced intrinsic contractility or dilation, whereas LV chamber compliance was not different from that of controls. LV hypertrophy was suggested by an increased ratio of LV mass to tibial length.…”
Section: Previous Studies In Animal Models Of Obesitymentioning
confidence: 93%
“…Nevertheless, such studies are limited. [5][6][7][8] Furthermore, most rodent models of obesity display features that are atypical of human disease, such as reduced fertility, altered linear growth, elevated levels of corticosteroids, and reduced lean body mass. These peculiarities limit their relevance for studies of cardiovascular pathophysiology.…”
mentioning
confidence: 99%
“…Each of the F 2 (SHR ϫ BN) rats in our population was phenotyped for BWadj-HW, which shows a strong correlation with blood pressure in rat models (43,55), including segregating populations of rats (reviewed in Ref. 47).…”
Section: Discussionmentioning
confidence: 99%